Excited-state proton-transfer reactions of 7-azaindole with water, ammonia and mixed water–ammonia: microsolvated dynamics simulation - Kerdpol,K. (Taylor and Francis Ltd., 2015)
© 2014 Taylor & Francis Dynamics simulations of excited-state multiple proton transfer (ESMPT) reactions in 7-azaindole (7AI) with ammonia, mixed water–ammonia, and water molecules were investigated by quantum dynamics simulations in the first-excited state using RI-ADC(2)/SVP-SV(P) in the gas phase. 7AI(WW), 7AI(WA), 7AI(AW) and 7AI(AA) clusters (W, water and A, ammonia) show very high probability of the excited-state triple proton transfer (ESTPT) occurrence in ranges from 20% for 7AI(WA) to 60% for 7AI(AW), respectively. Furthermore, 7AI(AW) clusters with ammonia placed near N–H of 7AI has the highest probability among other isomers. In 7AI with three molecules of bridged-planar of water, ammonia and mixed water–ammonia clusters, the excited-state quadruple proton transfer reactions occur ineffectively and rearrangement of hydrogen-bonded network on solvents also takes place prior to either ESTPT or excited-state double proton transfer. The role played by mixed-solvent is revealed with replacing H2O with NH3 in which the ESMPT is found to be more efficient corresponding to lower barrier in the excited state. The preferential number of solvent surrounding 7AI that facilitates the proton transfer process is two for methanol and water but this preferential number for ammonia is one. Highlights: (i) replacing H2O with NH3 assists ESPT corresponding to lower barrier in the excited state; (ii) the ESMPT time of 7AI with mixed water–ammonia is in the sub-picosecond timescale; (iii) the PT tends to be concerted process with at least one ammonia, but synchronous without ammonia.